When Place Matters: Shuttling of Enolase-1 Across Cellular Compartments - Didiasova, Miroslava; Schaefer, Liliana; Wygrecka, Malgorzata (Frontiers in Cell and Developmental Biology, 2019)
Enolase is a glycolytic enzyme, which catalyzes the conversion of 2-phosphoglycerate to phosphoenolpyruvate. Altered expression of this enzyme is frequently observed in cancer and accounts for the Warburg effect, an adaptive response of tumor cells to hypoxia. In addition to its catalytic function, ENO-1 exhibits other activities, which strongly depend on its cellular and extracellular localization. For example, the association of ENO-1 with the mitochondria membrane was found to be crucial for the stability of the mitochondrial membrane, and ENO-1 sequestration on the cell surface was crucial for plasmin-mediated pericellular proteolysis. The latter activity of ENO-1 enables many pathogens but also immune and cancer cells to invade the tissue, leading further to infection, inflammation or metastasis formation. The ability of ENO-1 to conduct so many diverse processes is reflected by its contribution to a high number of pathologies, including type 2 diabetes, cardiovascular hypertrophy, fungal and bacterial infections, cancer, systemic lupus erythematosus, hepatic fibrosis, Alzheimer´s disease, rheumatoid arthritis and systemic sclerosis. These unexpected non-catalytic functions of ENO-1 and their contributions to disease are the subjects of this review.